The dragon of Lonely Island - Rupp, Rebecca (New York : Scholastic., 2005)
Three children spend the summer with their mother on a secluded island where they discover a three-headed dragon living in a cave and learn what it means to be a Dragon Friend.
b
b
Keywords: Dragons -- Fiction; Siblings -- Fiction; Islands -- Fiction